Maximizing Weed Control in Florida Citrus - Stephen H. Futch (EDIS)
The objective of today's weed management program is to suppress and control weeds so that they do not cause damage to the tree, impact yield, or impede grove and harvesting operations. Complete and total elimination of all weeds from the grove floor is not necessary nor warranted. When developing a weed management program, growers must consider: 1) weeds present, 2) stage of weed growth, 3) material selection, 4) amount of herbicide used, 5) application site, method and timing, and 6) herbicide band width. These items are discussed in detail in this document. This document is HS-1007, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.